Muscle adaptations to aerobic training - Terjung, R. L. (1995)
1. Muscle adapts to aerobic exercise training to become a more effective energy provider. An improved capacity for oxygen extraction from the blood supply and an altered cellular control of energy metabolism likely contribute to the improved muscle performance evident with training. Of course, performance is also enhanced by improvements in maximal cardiac output and other adaptations not related to biochemical changes in the muscles. 2. Training adaptations are induced specifically in the muscles actively used in the exercise; these adaptations are sustained by continued activity and lost following inactivity. Both intensity and duration of exercise training sessions are important factors influencing muscle adaptations. 3. Although the development of optimal muscle adaptations is expected to enhance performance in competitive sport, meaningful adaptations developed in non-athletic populations by routine physical activity may also be important in promoting healthier living.